Nuclear Co-Localization of Expressional Products of CDK4&CDK6 and Human T Cell Lymphtropic Virus Type-1- Genes: An in Situ Hybridization and Immunohistochemical Study of Hodgkin’s Lymphoma Tissues from a Group of Iraqi Patients - Noor Sami AL- Lebawy (Journal of Global Pharma Technology, 2017)
Background Human T-cell leukemia/lymphoma virus type 1 (HTLV-1) infects 15-20 millions individuals worldwide. This on co retrovirus can be transmitted through 3 ways: horizontally, vertically (mother to child) and via blood transfusion. HTLV-1 causes 2 major diseases: Adult T-cell leukemia/lymphoma (ATLL) and tropical spastic par paresis/HTLV-1-associated myelopathy [1]. Although tumor cells exhibit rather infrequent mutations of cdk genes with the exception of G1 kinesis Cdk4 and Cdk6 amplification, over expression or hyper activation of basic cell cycle regulators is a general feature of human tumors [2]. Objective: To analyze the impact of concordant expression of cdk4, cdk6 and HTLV-1 infection on a group of tissues with Hodgkin’s lymphoma (HL). Patients and methods Eighty formalin-fixed, paraffin- embedded lymph node tissues were enrolled in this study; (40) biopsies from Hodgkin’s lymphoma (HL), and (40) lymph nodes with (unremarkable pathological changes) as apparently healthy controls. Detection of HTLV-1was done by ultra-sensitive version of in situ hybridization method whereas immunohisto chemistry detection system was used to demonstrate the expression of cdk4and cdk6 gene expression Results: The HBZ gene of HTLV-1positive – CISH reaction was detected in (22.5%: 9 out of 40 cases) of Hodgkin lymphoma tissues.NoHTLV-1 positive –CISH reaction was detected in healthy lymph nodes tissues of the control group. The differences between the percentages of HTLV-1 detection in HL tissues and control groups were statistically highly significant (P value = < 0.05). The positive cdk4&cdk6-IHC reactions were detected in 35% (14 out of 40 cases) and 57.5% (23 out of 40 cases) of Hodgkin lymphoma cases, respectively. A strong positive correlation was found between the detection, scores and intensity of cdk6 and cdk4markers. Conclusions: Significant expressions of both cdk6 and cdk4markersas well as HTLV-1 genes in Hodgkin’s lymphoma could indicate for their possible roles both in lymph node pathogenesis and carcinogenesis.Keywords: HTLV-1,Hodgkin’s lymphoma (HL), CDK6, CDK4, ISH, IHC.